International Practices of Auditing and Controlling Transfer Pricing - Fesenko Valeriіa V.; Myhal Yuliia I. (Problemi Ekonomiki, 2019)
The aim of the article is to analyze international practices in the field of auditing and controlling transfer pricing and determine the directions of its use in the practice of auditing and controlling in Ukraine. The globalization and European integration processes taking place in Ukraine have resulted in supplementing its legislation with international norms and rules in the field of preventing tax fraud in enterprises due to transfer pricing. The chronological sequence of introducing control over transfer pricing in different countries of the world is determined. Based on the analysis of international practices in the field of controlling transfer pricing, it is found out that 33 countries use the uncontrolled price method as a priority one, 9 countries use methods that differ from those recommended by the OECD Guidelines, 5 countries regulate the sequence of applying the methods, 2 countries do not use any of transfer pricing methods, and 2 countries use all the existing transfer pricing methods. The practices of foreign countries that have significantly improved their legislation as regards auditing and controlling transfer pricing can become the basis for the formation of an effective system of independent and state audit and control of transfer prices. The analysis of the legislation of various countries in the field of transfer pricing control and their practices allowed identifying diverse control methods, types of restrictions for external operations and types of controlled prices. This indicates the specificity of implementing transfer pricing control depending on the level of the country’s economic development, practices of tax control of the majority of powerful corporations, and the degree of involvement in international trade.